The Representation of Feminist Ideology in the Emirati Science Fiction in Arabic - Djeddai , Imen (Journal of Science and Knowledge Horizons, 2022)
In comparison to Western science fiction, there is a lack in the publication of science fiction novels in Arabic. The absence of Arab women characters leads Nora Al Noman, an author from the United Arab Emirates, to write her novel Ajwan. The writer shows the significant role of this genre in dealing with issues related to Arab women. This article aims to examine the characterization of the major female lead, Ajwan, in an alternative world and how she represents the feminist ideas. It focuses on the reaction of the protagonist to the concept of gender in a patriarchal society. Feminism is used as a theoretical framework to analyze the subversion of gender roles. In a post-apocalyptic world, Ajwan, who belongs to the Havaiki, experiences otherness in Al Zafir, However, she challenges marginalization and misogynist thought. Consequently, the major female lead becomes the empowered woman in her Arab community